178 Leadering during the COVID19 Pandemic: from medical student to CEO. (16th November 2020) - Baird, Hannah; Januszewski, Adam; Dominic, Cathy; Ogiliev, Tamzin; Feyi-Waboso, Joshua; Nurse, Kim; Whitehead, Christina; Hossain, Tan; Jawahar, Kaanthan; Wallace, Katie; Smith, Rebecca; Yassaee, Arrash Arya; et al.
Abstract : The FMLM Trainee Steering Group (TSG) sought to capture the lessons learnt through a series of interviews and blogs from individuals stepping forward into the leadership challenges during the COVID19 Pandemic. This included clinicians from Interim Foundation doctors through to chief executives to give a wide view of leadership-in-action and understand what lessons have been learnt so far from those individuals. This opportunity enabled those individuals to take stock and reflect on their own behaviours and of their team/organisation and was documented through a series of blogs. Each of the roles interviewed offered unique challenges and viewpoints. A thematic analysis analysing the behaviours and skills described was performed on the transcripts of these interviews and coded according to the domains from the FMLM standards. The transcripts were then coded using these categories and the percentage breakdown of each category identified and mapped to FMLM standards. Interviewees at all levels had experience or observed behaviours that represented the four overarching leadership domains as described by FMLM Leadership standards for healthcare professionals. There was awareness and experience at all levels up to and including systems leadership despite the individuals position. These interviews underline the importance of good leadership at times of crisis. Some interviewees displayed leadership behaviours that exceeded those that would normally be expected for their clinical position. Specific challenges relating to senior leaders included maintaining visibility and managing anxieties. Nearly all of the leaders interviewed said they were drawing on prior experience. Others interviewees reflected on the importance of having trust in your team and taking a collaborative approach to leading delivery of projects. Another consistent challenge across the interviews was the change to working virtually and how this can change the team dynamics.